Interactive art and the production of energy from the audience - Sogabe, Milton Terumitsu [UNESP]; Fogliano, Fernando; Peres, Carolina [UNESP]; Gazana, Cleber [UNESP]; Nunes, Fábio Oliveira [UNESP]; Steinberg, Mirian [UNESP]; Marques, Rodrigo Dorta [UNESP]; Nunes, Soraya Braz [UNESP] (My University, 2017)
This article presents reflections on the production and use of audience energy body in interactive installations. Mechanisms and symbolic-narrative meanings of the hand touch as well as the possibility of using the heat of the body as a poetic element and energy source in the work Toque are considered.
Keywords: Alternative Energy; Interactive Art; Touch